Effectiveness of Health Care System in the Controlling of Type (II) Diabetic Patients in Basra City - Al-Salman, H N K (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: Diabetes (diabetes mellitus [DM]) is a chronic disease affecting millions of people around the world with increment in its rate of incidence every year. Complications of diabetes are not only as health problem but also effect on the economic state of either patient himself or the whole society. Diabetes patients make several activities during their life because of DM, such as daily blood glucose measurement, regular physician visits, and others. In this study, we want to focus on the effect of health-care system and cost for the disease. Materials and Methods: This study involved the participation of 88 patients with diabetes type II. Their mean age was 53.37 ± 16.65. Mean body mass index was 31.17 ± 6.54. Several health status parameters were collected through specific formula made for this, method for measuring blood glucose level and patients’ monthly visits to the clinic or medical center were studied. Results: Health status of participated patients shows high level of glycated hemoglobin (HbA1c); the complications (neuropathy and blurred vision) were higher than other complications. Chronic diseases were associated with diabetes also seen. Patients on regular physician visit have lower HbA1c in compare with other patients. Conclusions: Diabetes needs further and continuous work to get good results in their health and continuous education to encourage measuring blood glucose measuring, notice any complication occurrence and regular with scheduled physician visits.